When women attack: Sex scandals, gender stereotypes, and candidate evaluations. (30th July 2015) - McLaughlin, Bryan; Davis, Catasha; Coppini, David; Kim, Young Mie; Knisely, Sandra; McLeod, Douglas
Abstract : The common assumption that female candidates on the campaign trail should not go on the attack, because such tactics contradict gender stereotypes, has not received consistent support. We argue that in some circumstances gender stereotypes will favor female politicians going negative. To test this proposition, this study examines how gender cues affect voter reactions to negative ads in the context of a political sex scandal, a context that should prime gender stereotypes that favor females. Using an online experiment involving a national sample of U.S. adults ( N=599 ), we manipulate the gender and partisan affiliation of a politician who attacks a male opponent caught in a sex scandal involving sexually suggestive texting to a female intern. Results show that in the context of a sex scandal, a female candidate going on the attack is evaluated more positively than a male. Moreover, while female participants viewed the female sponsor more favorably, sponsor gender had no effect on male participants. Partisanship also influenced candidate evaluations: the Democratic female candidate was evaluated more favorably than her Republican female counterpart.